Numerical model of three‐dimensional coupled wall structures - Czesław Miedziałowski; Tadeusz Chyży; Joanna Krętowska (Journal of Civil Engineering and Management, 2007)
Three‐dimensional description of a building structure taking into consideration the soil structure interaction is a very complex problem; the solution of it is often obtained by the finite‐element method. However, this method takes a significant amount of computational time and memory. Therefore an efficient computational model based on the subdivision of the structure into building elements such as wall and floor slab elements, plane and three‐dimensional joints and lintels, that could provide accurate results with a significantly reduced computational time, is proposed in this study for the analysis of three‐dimensional structures. The examples prove the efficiency and the computing possibilities of the model.